Variasi Penempatan Bronjong Di Hilir Kolam Olak Terhadap Pola Gerusan Dasar: Variations in the Placement of Gabions in the Downstream of the Pool Against Basic Scouring Pattern - I Dewa Gede Jaya Negara; Salehudin Salehudin; Lilik Hanifah; I Wayan Yasa; Ni Putu Ira Sintia Kurnianti (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
The existence of a weir is often disrupted by the occurrence of scouring downstream, which results in an insecure weir position. This study aims to determine the effect of installation of gabion variations downstream of stilling ponds on the depth and length of scour at the bottom of the channel. The test was carried out at the Hydrology and Coastal Laboratory of FT Unram in a straight channel with dimensions of 7.5 m x 0.55 m x 0.5 m, with an Ogee type spillway and a USBR Type III stilling pond. The dimensions of the test gabions are 0.55 m x 0.18 m x 0.09 m with a gravel diameter of 1 (P1 ) 0.035 m, (P2 ) 0.0175 m and (P3 )0.00875 m, and the variation of discharge 1(Q1) 0.0019 m3/s, discharge 2(Q2) 0.0036 m3/s, discharge 3 (Q3) 0.0047 m3/s and discharge 4 (Q4) 0.0065 m3/s. The results showed that in conditions without gabions, scour was prone to occur near the end of the stilling pond to the center of the channel bottom and towards the right side of the channel, with a scour depth of 0.002m – 0.023m and a length of 0.075m – 0.45m. For conditions with gabions, the scour length ranges from 0.15m – 0.275m with a depth of 0.0016m – 0.026 m, the scour occurs more evenly to the left and right of the channel.